Dynamic Stability of a Cantilevered Timoshenko Beam on Partial Elastic Foundations Subjected to a Follower Force - Ryu, Bong-Jo; Shin, Kwang-Bok; Yim, Kyung-Bin; Yoon, Young-Sik (Journal of mechanical science and technology, 2006)
This paper presents the dynamic stability of a cantilevered Timoshenko beam with a concentrated mass, partially attached to elastic foundations, and subjected to a follower force. Governing equations are derived from the extended Hamilton's principle, and FEM is applied to solve the discretized equation. The influence of some parameters such as the elastic foundation parameter, the positions of partial elastic foundations, shear deformations, the rotary inertia of the beam, and the mass and the rotary inertia of the concentrated mass on the critical flutter load is investigated. Finally, the optimal attachment ratio of partial elastic foundation that maximizes the critical flutter load is presented.[PUBLICATION ABSTRACT]